The association between poor sleep quality and cardiometabolic risk in HIV+ individuals and the general population living in a rural area of South Africa - Reddy, Tracy (University of the Witwatersrand, Johannesburg, 2024)
Studies show that both poor sleep quality and HIV infection independently increase cardiometabolic risk (CMR). Additionally, poor sleep quality is common with HIV infection. Our study investigated whether HIV infection interacts with poor sleep quality to affect CMR in people living with HIV (PLWH) in a rural area of South Africa. We recruited 200 HIV+ participants and 200 controls from Qwa Qwa in Free State in South Africa and assessed their CMR, sleep quality, daytime sleepiness, risk of obstructive sleep apnoea and degree of depressive symptoms. Sleep quality (p = 0.15), daytime sleepiness (p = 0.31) and the cardiometabolic risk score (MetScore) (p = 0.93) were similar between HIV+ and control participants. Fewer HIV+ participants had a high risk of sleep apnoea (p = 0.019) but more HIV+ participants had symptoms of clinical depression (p = 0.0007). Poorer sleep quality in the HIV+ participants was associated with pain (p = 0.0006), more severe depressive symptoms (p<0.0001) and longer HIV duration (p = 0.011). However, HIV infection was not associated with a higher MetScore (p = 0.18) once age, sex and sleep and depression markers were adjusted for. Additionally, HIV infection increased the risk of hypertension (p = 0.016). HIV status did not interact with sleep quality (p = 0.32) to affect CMR. Our findings indicate that healthcare facilities should consider monitoring CMR factors in HIV+ individuals.
A research report submitted in fulfillment of the requirements for the Master of Science in Medicine, in the Faculty of Health Sciences, School of Physiology, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; sleep quality; cardiometabolic risk; HIV; rural; South Africa; depression; metabolic syndrome; obstructive sleep apnoea; SDG-3: Good health and well-being